Beach debris quantity and composition around the world: A bibliometric and systematic review. (May 2022) - Ansari, Mohsen; Farzadkia, Mahdi
Abstract: Anthropogenic pollution of marine ecosystems caused by beach debris has become a serious environmental concern in the last few decades. Regarding the raising production of beach debris, the present work aimed to summarize the quantity and quality of beach debris reported from different beach areas of the world. Also, a bibliometric analysis was used to analyze research trends and upgrade knowledge in this research area. Using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), the eligible papers reviewed regarding beach debris abundance along with their composition from 2010, which were extracted from the Scopus database. The results of the study showed that plastic items represented the dominant material (61.25%), followed by food (5.88%), wood (5.78%), metals (5.2%), and glass (5%). Further, the beaches studied were classified into three degrees, including highly polluted (31.5 items/m 2 ), moderate polluted (3.47 items/m 2 ), and low polluted (0.37 items/m 2 ), based on the average abundance of debris. Graphical abstract: Unlabelled Image Highlights: Scientific literature on beach debris increased considerably after 1998. Beach debris research can be organized in 6 clusters by keywords analysis. Abundance and composition of beach debris in the world were summarized. Beaches studied were classified regarding their debris abundance.